Effect of The Macro-Environment Factors On the Relationship Between Firm Resources and Export Performance of Small and Medium Scale Manufacturing Enterprises in Nairobi City County, Kenya - Kitonyi, Samson; Kibera, Francis; Gathungu, James; Yabs, John (European Scientific Journal, ESJ, 2020)
The aim of this study was to evaluate the influence of macro-environmental factors on the relationship between firm resources and the export performance of small and medium-sized manufacturing enterprises in Nairobi City County, Kenya. The study was based on cross sectional research design. A total of 265 out of 853 firms formed the study sample. Data was collected via a structured questionnaire. The response rate was 89.1 percent. Descriptive statistics and inferential analysis (step wise bivariate and multiple regression) was used to achieve the study objective. A five percent level was preferred in testing significance of the coefficients. The findings revealed that macro-environmental factors significantly moderated the relationship between firm resources and the export performance of small and medium-sized manufacturing enterprises in Nairobi City County, Kenya. For the firm to improve its export performance, the study recommends that firms have to take stock of firm specific resource endowments and respond to changes in the macro environment within which they operate. Also, exporting organizations must match firm innovativeness levels to external environmental conditions and internal capabilities and structures.